Satellite‐derived surface temperature and in situ measurement at Solfatara of Pozzuoli (Naples, Italy). (18th June 2016) - Silvestri, M.; Cardellini, C.; Chiodini, G.; Buongiorno, M. F.
Abstract: Ground thermal anomalies in volcanic‐hydrothermal systems, where the outflow of hot fluids gives rise to fumarolic fields, soil degassing, and hot soils, have, up to now, rarely been investigated by using satellite. Here we report a comparison between surface temperature derived by satellite data and a large data set of measured soil temperatures and CO2 fluxes for a volcanic‐hydrothermal system, the Solfatara of Pozzuoli (Campi Flegrei, Italy). Surface temperatures derived from ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) data are compared with soil temperatures and CO2 fluxes from four surveys performed in 2003, 2010, and in 2014. The good match between the spatial distributions of computed and measured temperatures suggests the adequacy of satellite data to describe the Solfatara thermal anomaly, while the correspondence between temperatures and CO2 fluxes, evidences the link between degassing and heating processes. The ASTER derived surface temperatures (14–37°C) are coherent with those measured in the soil (10–97°C at 10 cm depth), considering the effect of the thermal gradients which characterize the degassing area of Solfatara. This study shows that satellite data can be a very powerful tool with which to study surface thermal anomalies, and can provide a supplementary tool to monitor thermal evolution of restless volcanoes. Key Points: ASTER‐derived surface temperature is compared with in situ soil temperatures and CO2 fluxes Correlations between ASTER‐derived results and both in situ temperatures and CO2 fluxes Relationship between the degassing process and the heating of the soil at Solfatara of Pozzuoli